(untitled) (Pakistan Journal of Social Research, 2022)
Since the beginning of the 21st century, the world has witnessed a new wave of rising religious and national fundamentalism. The fundamentalist ideas of superiority of religion, race, and ethnicity have been reignited in the minds of common people by many politicians across the world. Owing to the fundamentalist ideas of India’s far-right Bharatiya Janata Party, India, and its neighboring countries are also witnessing a new radical mindset in the region that is leading this region towards a pitfall of disastrous instability. In the following lines, there will be an attempt to understand how fundamentalism can be disastrous for any State and what repercussions can Indian democracy, society, its immediate neighbors, and the world at large can face in the wake of rising Hindutva fundamentalism therein. Keywords: Fundamentalism, Hindutva, BJP, Ideology, Secularism, Indian Constitution, Destabilization.